2000
DOI: 10.1046/j.1365-2761.2000.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of experimental amoebic gill disease in Atlantic salmon, Salmo salar L., and the effect of pre‐maintenance of fish in sea water on the infection

Abstract: Atlantic salmon were exposed to amoebic gill disease (AGD) immediately following their acclimatization to sea water (group 1), or following a 2 week period of maintenance in sea water (group 2). Three fish from each group were sampled on days 0, 1, 2, 4, 7, 14 and 28 post‐infection. Characteristic gill lesions began to occur between days 2 and 4, and dramatically increased by day 7. The number of gill lesions on fish from group 2 was significantly higher than on fish from group 1 on days 7 and 14 (P<0.001), bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 8 publications
7
64
2
Order By: Relevance
“…The parasome has been identified as a symbiotic organism, Perkinsiella amoebae (Dyková et al 2000), and is found in a variety of amoeba species. Additionally Neoparamoeba has been shown to be Alcian blue positive (Zilberg & Munday 2000). Immunofluoresce staining procedures have been developed for identification of this parasite in gill smears and sections (Howard & Carson 1993).…”
Section: Taxamentioning
confidence: 99%
“…The parasome has been identified as a symbiotic organism, Perkinsiella amoebae (Dyková et al 2000), and is found in a variety of amoeba species. Additionally Neoparamoeba has been shown to be Alcian blue positive (Zilberg & Munday 2000). Immunofluoresce staining procedures have been developed for identification of this parasite in gill smears and sections (Howard & Carson 1993).…”
Section: Taxamentioning
confidence: 99%
“…In addition to N. pemaquidensis, the closely related N. aestuarina should be taken into consideration as well as a supposed third Neoparamoeba species (Fiala and Dyková 2003). The data accumulated on pathogenicity of the AGD agent in Atlantic salmon and on host-parasite relationships (Findlay et al 1998, Clark and Nowak 1999, Zilberg et al 1999, Douglas-Helders et al 2000, 2001b, 2002, Zilberg and Munday 2000, Adams and Nowak 2001, Elliot et al 2001) strongly influence the search for potential pathogens among other amoebae.…”
Section: Gill-infecting Speciesmentioning
confidence: 99%
“…Gill pathology of AGD-affected fish involves epithelial hyperplasia, as well as mucous cell hyperplasia and an extensive mucus secretion (Munday et al 1990, Nowak & Munday 1994, Zilberg & Munday 2000, Roberts & Powell 2003a. It has been previously suggested that excessive branchial mucus impairs CO 2 excretion, leading to respiratory acidosis and subsequent death in AGD affected fish (Powell et al 2000).…”
Section: Introductionmentioning
confidence: 99%